STUDI PREFORMULASI TABLET EFFERVESCENT DAUN TORBANGUN (Coleus Amboinucus L) SEBAGAI ALTERNATIF PENINGKATAN PRODUKSI ASI - Nur Rahmawati Sholihah; Kurnia Rahayu Purnomo Sari (Politeknik Kesehatan Kementerian Kesehatan Banten, 2022)
The prevalence of exclusive breastfeeding coverage is still far from the national target. The lack of utilization torbangun leaves an excellent opportunity for the development of science and technology. This study aims to determine the optimum formulation of torbangun leaf effervescent tablets (Coleus Amboinicus L) as an alternative to increasing breast milk production. The research method used was an experimental post-experimental design, with the stages of processing simplicia, extracting torbangun leaves, making effervescent tablet formulas, evaluating granules, and evaluating tablet preparations. The difference in the dose variation of each ingredient used in the manufacture of the torbangun leaf effervescent tablet formula greatly affects the quality which is reviewed based on the moisture test of the formulation and the physical properties of the torbangun leaf granules. The results shown in table 2, obtained the formulation of torbangun leaf effervescent tablets made with a variety of ingredients with 4 formulas with a weight of 100 grams each, from the 4 formulas arranged, the results obtained that the best effervescent tablet formula was found in formula 4. A good formula was then tested for granule moisture, flow properties test for an angle of repose and compressibility index as an effervescent tablet in increasing breast milk production, the Na Bicarbonate content in formula 4 which was 26.56 grams gave an excellent solubility effect in water, with this the galactagogue content in Torbangun extract is more free and effective for breast milk production. Meanwhile, based on the physical properties of the granules, the best granule physical properties is formula 2 with a good flow rate, which is more than 10g/second. The flow rate of a granule is influenced by the shape of the granule and the size of the granule.